2011
DOI: 10.1038/bmt.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated cord blood transplantation for thalassaemia: a single-institution experience of 35 patients

Abstract: Our study was designed to prospectively determine whether or not unrelated cord blood transplantation (CBT) can produce outcomes comparable to related donor transplantation for children with b-thalassaemia. In 35 patients, 40 transplants were performed between October 2003 and September 2009. HLA matching at enrolment was 6/6 (n ¼ 8), 5/6 (n ¼ 16), 4/6 (n ¼ 27), or 3/6 (n ¼ 1) by low-resolution HLA-A, -B, and high-resolution DRB1. These patients received non-manipulated grafts without ex vivo expansion or T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 26 publications
(26 reference statements)
3
48
0
1
Order By: Relevance
“…Compared with these aforementioned studies, our follow-up time was shorter and the age of our patients was younger. Our results were also comparable to the outcomes of Jaing et al 22 for unrelated cord blood transplants for patients with TM: of the 40 unrelated cord blood transplants that were studied, the 5-year OS and TFS was 88.3% Ϯ 6.7% and 73.9% Ϯ 7.4%, respectively, and the cumulative incidence of TRM at 2 years was 11.7% Ϯ 6.7%.…”
Section: Discussionsupporting
confidence: 77%
“…Compared with these aforementioned studies, our follow-up time was shorter and the age of our patients was younger. Our results were also comparable to the outcomes of Jaing et al 22 for unrelated cord blood transplants for patients with TM: of the 40 unrelated cord blood transplants that were studied, the 5-year OS and TFS was 88.3% Ϯ 6.7% and 73.9% Ϯ 7.4%, respectively, and the cumulative incidence of TRM at 2 years was 11.7% Ϯ 6.7%.…”
Section: Discussionsupporting
confidence: 77%
“…These remarkably good results are likely attributable to the high number of total nucleated cells/kg infused (7.8x10 7 /kg). 44 Combining data from 3 different registries, Ruggeri et al found the outcome of UCBT in TM to be much less favorable; in 35 TM patients, an OS of 62% with a DFS of only 21% was reported. The cumulative incidence of graft failure was 52%.…”
Section: Unrelated Cord Blood Transplantationmentioning
confidence: 99%
“…10,11 The development of new techniques to improve the management of graft versus-host disease (GVHD), and to perform HSCT from unrelated donors or cord blood stem cells may expand the pool of potential donors in the near future; currently they remain largely investigational. [12][13][14] Because of these significant disadvantages, and shortage of suitable donors, HSCT is limited to less than one third of the patients; for the vast majority of thalassemic subjects lacking an HLA-matched donor, clinical improvement or even a final cure might be achieved by gene therapy approaches.…”
Section: Allogeneic Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%